ANALISIS DINAMIKA DAN FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI UDANG WINDU PETAMBAK PLASMA PADA SISTEM KEMITRAAN DENGAN PT. CENTRAL PERTIWI BAHARI PROVINSI LAMPUNG - Aviati S., Yuniar; Abbas Z, Wan (Lampung University)
The objective of this research are (1) to analyzed groups dinamic level of shrimp farmer, (2) to compute factors influencing shrimp production in P.T. Central Pertiwi Bahari. This study employs survey method, involving 310 shrimp farmers as respondents. The respondents were selected using stratified random sampling, in which the stratification was based on production average. The group dynamic was analyzed in descriptive qualitative analysis where as production analysis was using Cobb-Douglas production function. The study shows that group dynamic level of shrimp farmer were at medium level, and the interaction between the company and the shrimp farmer were generally good. The avarage shrimp production was 2,74 ton/ha which was relatively low as compare to their potential production which is around 4-6 ton/ha. The production factors that have positive effect to the shrimp production were labor absorption, quantity of feeds, and quanitity of fertilizers. However, the use antibiotic treatment was causing a reduction on shrimp production.